2021
DOI: 10.3390/foods10020369
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Apulian Olive Biodiversity: The Case of Oliva Rossa Virgin Olive Oil

Abstract: In this study, the drupes and virgin olive oils extracted from the Oliva Rossa landrace are characterized. Oliva Rossa is an old landrace part of the autochthonous Apulian olive germplasm for which only few data have been reported till now. During the study, the maturity patterns of the drupes had been followed. Four samplings per year were planned, one every 14 days starting from the middle of October. The pigmentation index, the oil content and the total phenolic content of the drupes were measured. Simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
1
12
0
1
Order By: Relevance
“…This phenomenon, called véraison, literally means a change of color, and is used as an indicator of the ripening stage. Olive farmers start harvesting the olives when they are in the middle of véraison, before full ripeness [ 13 ]. The change of color is due to chlorophyll loss and a concomitant increase in anthocyanin pigmentation [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon, called véraison, literally means a change of color, and is used as an indicator of the ripening stage. Olive farmers start harvesting the olives when they are in the middle of véraison, before full ripeness [ 13 ]. The change of color is due to chlorophyll loss and a concomitant increase in anthocyanin pigmentation [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this scenario, Italy and its very rich olive germplasm—estimated to include about 800 cultivars—play a dominant role, not only in the preservation of olive biodiversity, but also in the production of high-quality olive oils with strong sensory specificity [ 8 , 9 ]. In recent years, several studies have focused on the rediscovery and valorization of minor local Italian cultivars in an attempt to provide valuable genetic resources to be used as strategic elements to increase the sustainability of the future of oil production, pursuing, at the same time, enrichment and diversification of EVOOs to be placed on the market [ 5 , 7 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Myristic (C14:0), heptadecanoic, and eicosanoic acids are also present in small amounts [ 6 , 7 , 8 , 9 , 12 , 13 , 14 ]. See Table S1 for further information on the percentages of fatty acids present in EVOO from the main cultivars in the Mediterranean Area [ 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Triglycerides (TAGs) account for 99% of the saponifiable fraction.…”
Section: Resultsmentioning
confidence: 99%
“…Smaller amounts of simpler phenolic compounds—such as caffeic, vanillic, and ferulic acids—have the role of protecting and enhancing the bioavailability of α-tocopherol [ 6 , 7 , 8 , 9 , 12 , 13 , 14 , 33 , 34 ]. See Table S2 for further information regarding antioxidants in the unsaponifiable fraction of EVOO from the main cultivars in the Mediterranean Area [ 17 , 19 , 20 , 21 , 22 , 23 , 25 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Chlorophyllic and carotenoid pigments.…”
Section: Resultsmentioning
confidence: 99%
“…Four minor Italian cultivars were exploited by Piscopo et al [3] to improve extra virgin olive oil (EVOO) production in the Calabria region; they obtained in most cases good quality oil in terms of free acidity, peroxides, spectrophotometric indexes, fatty acid composition, and bioactive compounds. Squeo et al [4] investigated the cultivar "Oliva Rossa", which represents an old landrace belonging to the autochthon Apulian olive germplasm. The authors showed that the extracted virgin olive oils had a medium to high level of oleic acid.…”
mentioning
confidence: 99%